Global algorithm for the endovascular treatment of chronic femoropopliteal lesions: an interdisciplinary expert opinion statement - Korosoglou, Grigorios; Schmidt, Andrej; Lichtenberg, Michael; Malyar, Nasser; Stavroulakis, Konstantinos; Reinecke, Holger; Grözinger, Gerd; Patrone, Lorenzo; Varcoe, Ramon L.; Soukas, Peter A.; Böckler, Dittmar; Behrendt, Christian-Alexander; et al. (JACC Cardiovascular interventions, 2025)
A global treatment algorithm was developed for the endovascular revascularization of femoropopliteal lesions and chronic total occlusions, aiming toward a more standardized approach to endovascular treatment in patients with peripheral artery disease. The following steps are proposed. 1) Evaluation of lesion morphology based on preprocedural imaging by Duplex sonography and intravenous ultrasound for selection of lesion preparation tools. Lesion characteristics are mainly defined by calcification, lesion length, and the presence of total occlusion and in-stent restenosis. 2) Selection of vessel preparation strategies, which encompass plain old balloon angioplasty, atherectomy, thrombectomy, intravascular lithotripsy and specialty balloons, or a combination of the preceding, based on lesion and patient-specific characteristics. In addition, a Delphi consensus was applied for the appropriateness of lesion preparation strategies, depending on lesion anatomy, length, plaque morphology, and subintimal versus intraluminal guidewire crossing. 3) Definitive lesion treatment strategies using drug-coated balloons, bare-metal stents, drug-eluting stents, and/or covered stents or a combination. By establishing this treatment algorithm in routine practice, improvements in vessel- and patient-specific outcomes are anticipated, which will be further enhanced by continuous collaboration among experts from different countries and disciplines and by randomized controlled trials.
Online verfügbar: 10. März 2025
Gesehen am 09.09.2025